Aldosterone/direct renin concentration ratio as a screening test for primary aldosteronism: A meta-analysis. (July 2016) - Li, Xiyue; Goswami, Richa; Yang, Shumin; Li, Qifu
Objective: The accuracy of aldosterone/direct renin concentration ratio (ADRR) as a screening test in patients with primary aldosteronism (PA) varies widely across the studies. Therefore, we conducted a meta-analysis to assess the accuracy of ADRR. Methods: A literature search was performed in PubMed, Embase, and the Cochrane library published between April 1971–February 2016. Studies focusing on the accuracy of ADRR for PA screening were included. Two authors independently extracted information regarding patient characteristics, antihypertensives status, true positives, true negatives, false positives, and false negatives. The random-effects model was used for statistical analysis. Heterogeneity was explored by subgroup analysis and meta-regression. Results: Nine studies involving 974 patients were included. The overall sensitivity, specificity, area under the curve, and diagnostic odds ratio of ADRR were 0.89 (95% confidence interval (CI) 0.84–0.93), 0.96 (95% CI 0.95–0.98), 0.985 and 324 respectively, with substantial heterogeneity. Meta-regression showed that antihypertensive status affects the ADRR and may account for the heterogeneity ( p =0.03). Subgroup analysis of patients who discontinued the antihypertensives revealed a sensitivity of 0.99 (95% CI, 0.95–1.00) and a specificity of 0.98 (95% CI, 0.96–0.99). Conclusions: This study demonstrates the efficacy of ADRR as a screening test for PA. However, as antihypertensive drugs can interfere with the interpretation of ADRR, it is recommended to interrupt therapy or at least replace with analogues that do not significantly affect the ADRR value.